Older Adolescents and Young Adults With Autism Spectrum Disorder Have Difficulty Chaining Motor Acts When Performing Prehension Movements Compared to Typically Developing Peers - Fukui, Takao; Sano, Misako; Tanaka, Ari; Suzuki, Mayuko; Kim, Sooyung; Agarie, Hiromi; Fukatsu, Reiko; Nishimaki, Kengo; Nakajima, Yasoichi; Wada, Makoto (Frontiers in Human Neuroscience, 2018)
It is known that motor actions performed by individuals with autism spectrum disorders (ASD) are clumsy and a previous study revealed that children with ASD of around eight years old showed less smooth movement and dysfunction of appropriate usage of online vision for grip aperture control. The present study investigates whether and how the kinematic properties of reach-to-grasp movements in older adolescents and adults with ASD [mean (± SD) age: 18.3 ± 2.1] differ from those in typically developing (TD) peers [mean (± SD) age: 19.1 ± 2.2]. Revealing the kinematic properties of reach-to-grasp movements in older adolescents and adults with ASD is indispensable in determining the developmental trajectory of this motor behavior in individuals with ASD. While wearing liquid crystal shutter goggles, participants reached for and grasped a cylinder with a diameter of either 4 cm or 6 cm. Two visual conditions were tested: a full vision (FV) condition (the goggles remained transparent during the movement) and a no vision (NV) condition (the goggles were closed immediately after the movement was initiated). These two visual conditions were either alternated with each trial in a single experimental session (alternated condition) or blocked within the session (blocked condition). We found that the reaching movement smoothness calculated as a normalized jerk score (i.e., index of skilled, coordinated human movements) of ASD participants did not differ significantly from that of TD peers although ASD participants showed smoother reaching in the alternated condition than in the blocked condition. The influence of online vision and its visual condition schedule on grip aperture during the in-flight phase was remarkably similar between the ASD and TD groups. Furthermore, we found that ASD group experienced a significant longer transition period from grasping end (i.e., stable holding when touching the surface of the object) to uplift initiation than the TD group. The results suggest that 1) deficits in movement smoothness and the use of online vision for motor control are rectified by the time individuals with ASD reach late adolescence and 2) older adolescents and adults with ASD still have difficulties chaining motor acts.